2013
DOI: 10.1371/journal.pone.0057393
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Canonical and Up-Regulation of Non-Canonical Wnt Signalling in the Carcinogenic Process of Squamous Cell Lung Carcinoma

Abstract: The majority of lung cancers (LC) belong to the non-small cell lung carcinoma (NSCLC) type. The two main NSCLC sub-types, namely adenocarcinoma (AC) and squamous cell carcinoma (SCC), respond differently to therapy. Whereas the link between cigarette smoke and lung cancer risk is well established, the relevance of non-canonical Wnt pathway up-regulation detected in SCC remains poorly understood. The present study was undertaken to investigate further the molecular events in canonical and non-canonical Wnt sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 41 publications
(38 reference statements)
2
36
0
Order By: Relevance
“…Aggregates were grown in SAGM/EGM-2/FGM-2 media at 2:2:1 ratio. After 24 h 3D aggregates were transferred on a 24 well plate (also coated with poly-HEMA) and treated with recombinant human Wnt5a at final concentration of 1 μg/ml for 72 h (Chinese Hamster Ovary Cell Line, CHO-derived Gln38-Lys380) (R&D Systems, Minneapolis, USA) [23], cisplatin (Selleck Chemicals, Houston, USA) (29.7 μM for 72 h) [25], IWR-1 (Sigma Aldrich, St. Louis, USA) (1 μM for 3 h) [23] and LiCl (Sigma Aldrich, St. Louis, USA) (10 mM for 3 h) [29]. Upon treatment they were collected in RA1 Buffer Solution for RNA isolation, into cryostat embedding medium for dissection or used for drug transporter functional test.…”
Section: D Lung Aggregate Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregates were grown in SAGM/EGM-2/FGM-2 media at 2:2:1 ratio. After 24 h 3D aggregates were transferred on a 24 well plate (also coated with poly-HEMA) and treated with recombinant human Wnt5a at final concentration of 1 μg/ml for 72 h (Chinese Hamster Ovary Cell Line, CHO-derived Gln38-Lys380) (R&D Systems, Minneapolis, USA) [23], cisplatin (Selleck Chemicals, Houston, USA) (29.7 μM for 72 h) [25], IWR-1 (Sigma Aldrich, St. Louis, USA) (1 μM for 3 h) [23] and LiCl (Sigma Aldrich, St. Louis, USA) (10 mM for 3 h) [29]. Upon treatment they were collected in RA1 Buffer Solution for RNA isolation, into cryostat embedding medium for dissection or used for drug transporter functional test.…”
Section: D Lung Aggregate Culturesmentioning
confidence: 99%
“…Previous studies have shown that Wnt pathway, although rarely mutated, is differentially regulated in LC subtypes. While beta-catenin dependent signaling can be strongly down-regulated in SCLC through over-expression of inhibitory genes differential activation of the beta-catenin dependent canonical and Ca 2+ dependent non-canonical Wnt pathways have been reported in NSCLC subtypes of AC and SCC, respectively [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Li [47] noted that WISP1 enhances alveolar capillary permeability in ALI and Konigshoff et al [63] demonstrated that anti-WISP1 antibodies attenuated bleomycin-induced lung fibrosis. Fewer reagents and progress in the lung with respect to the non-canonical pathway is apparent, although detection of hallmark regulatory proteins WNT5A or WNT11 suggests this pathway may be operative in certain forms of lung cancer [64]. Although the original observations by Slutsky et al [65,66] concluded that WNTβ-catenin signaling is important in VILI, they reported increases in indices of activation of both non-canonical (WNT5A) and canonical pathways in whole rat lung.…”
Section: Wisp1 and The Wnt Pathwaymentioning
confidence: 99%
“…Fewer reagents and progress in the lung with respect to the non-canonical pathway is apparent, although detection of hallmark regulatory proteins WNT5A or WNT11 suggests this pathway may be operative in certain forms of lung cancer [64]. Although the original observations by Slutsky et al [65,66] concluded that WNTβ-catenin signaling is important in VILI, they reported increases in indices of activation of both non-canonical (WNT5A) and canonical pathways in whole rat lung. Further confirmative studies are required to identify which WNT signaling pathway is responsible for WISP1 production in the lung.…”
Section: Wisp1 and The Wnt Pathwaymentioning
confidence: 99%
“…Moreover, it has been demonstrated that activation of canonical Wnt signaling, in xenopus axis formation required the formation of Wnt11 and Wnt5a tyrosine-sulfated oligomers. Bartis et al (2013) identified Wnt11 and Wnt5a as regulators of cadherin expression and potentiated relocation of β-catenin to the nucleus as an important step in decreased cellular adhesion of squamous cell lung carcinoma. Thus, we sought to determine the role of Wnt11 in SKOV-3 cells and its possible modulation by Wnt5a in SKOV-3/Wnt5a cells.…”
Section: Substrate-dependent Cell Adhesion Assay In the Presence Of Rmentioning
confidence: 99%